Structure–activity relationships of proline modifications around the tetracyclic-indole class of NS5A inhibitors. Issue 21 (1st November 2016) - Tong, Ling; Yu, Wensheng; Coburn, Craig A.; Chen, Lei; Selyutin, Oleg; Zeng, Qingbei; Dwyer, Michael P.; Nair, Anilkumar G.; Shankar, Bandarpalle B.; Kim, Seong Heon; Yang, De-Yi; Rosenblum, Stuart B.; et al.
Graphical abstract: Abstract: We describe the impact of proline modifications, in our tetracyclic-indole based series of nonstructural protein 5A (NS5A) inhibitors, to their replicon profiles. This work identified NS5A inhibitors with an improved and flattened resistance profiles.